PELEMBAGAAN DEMOKRASI DAN PENGUATAN CIVIL SOCIETY MELALUI PENDIDIKAN: HARAPAN TERHADAP PESANTREN - Syamsul Arifin (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
Democrat' institutionalkation and civil society encouragement need a prerequisite, namely an integration between state and community elements. The unification of them will create a democratic political culture, namely, democratic civility. This a,pect of civility is significant to minimize primitive political behaviors causing a democratic civility vacuum. This vacuum is a result of neglecting an urgency of democracy education. Democrag, as an ideology, thrives by not only relying on natural process but also studying and practicing it continually. In this context, therefore, education owned by Moslems as that implemented in Pesantrens is one of important institutions that may build a democrat' education.